Life history and larval chaetotaxy of Ahmetia achaja (Lepidoptera, Lycaenidae, Lycaeninae, Theclini, Cheritrina) - Ballmer, Gregory R.; Wright, David M. (Zootaxa, 2008)
Aspects of the life history of Ahmetia achaja (Fruhstorfer) and a description of the immature stages are presented. Larval chaetotaxy and morphological features of the eggs and pupae suggest a close phylogenetic relationship with some other members of the subtribe Cheritrina.